A Sociolinguistic Analysis of Insulting Language in Indonesian Online Media - Salsabila As Shofi; Dwi Anggoro Hadiutomo (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
This study investigates how insulting language is used in Indonesian online media and how it reflects social context through the lens of register theory. The research aims to examine how the use of offensive terms such as bodoh, tolol, goblok, and dungu varies according to field, tenor, and mode, and how these variations relate to the speaker's role and communicative purpose. The study analyzed 20 utterances containing insulting language, quoted in news articles published on detik.com between January and June 2025. The data were purposively sampled to include diverse speakers, netizens, religious leaders, political figures, and commentators, allowing the study to capture linguistic variation across social roles. Using a qualitative descriptive approach, the study employed manual content analysis based on Halliday’s (1978) theory of register. Each utterance was examined in relation to its field, tenor, and mode. The results show that netizens tend to use insults as spontaneous expressions of emotion and group alignment, while public figures use similar language more strategically, either to persuade, criticize, or assert authority. Religious and political leaders, for example, use offensive terms rhetorically within moral or ideological discourse, revealing that insulting language is not always intended to harm but can also serve as a tool for emphasis, contrast, or resistance. The study concludes that offensive language in digital media is deeply shaped by social context and communicative intent. These findings contribute to sociolinguistics and applied communication by demonstrating how language, especially in its harshest forms; constructs identity, authority, and meaning in contemporary digital interaction.